Analytical methods : interpretation, identification, quantification - Gopalan, R. (Universities Press, 2018)
"The concepts that students learn in classrooms and the experiments they do in the laboratory are hardly ever integrated in the existing teaching methodology. This textbook on Analytical Methods is written with a view to addressing this lacuna. The main topics in analytical chemistry are dealt with—gravimetric analysis, volumetric analysis, separation and purification techniques, data analysis, thermoanalytical methods and various types of spectroscopy. Detailed discussions on new spectroanalytical techniques, polarimetry, laser techniques, Mössbauer spectroscopy and fluorescence spectroscopy are presented. The main objective is to introduce students to existing methods of analysis, new techniques, their instrumentation and mainly their applications, giving them an insight into this challenging and fascinating field. This book will serve as a text for students of M.Sc. chemistry. In addition, it can serve as a convenient reference for B.Sc. chemistry students and for candidates taking the UGC–CSIR NET examination."